Positivity bias in past and future episodic thinking: Relationship with anxiety, depression, and retrieval-induced forgetting. Issue 3 (March 2019) - Marsh, L; Edginton, T; Conway, MA; Loveday, C
Positivity biases in autobiographical memory and episodic future thinking are considered important in mental wellbeing and are reduced in anxiety and depression. The inhibitory processes underlying retrieval-induced forgetting (RIF) have been proposed to contribute to these biases. This investigation found reduced positivity in past and future thinking to be associated with reduced memory specificity alongside greater levels of anxiety, depression, and rumination. Most notably, however, RIF was found to significantly predict memory valence. This indicates that RIF may be important in maintaining such biases, facilitating the forgetting of negative memories when a positive item is actively retrieved.